2020
DOI: 10.1097/fm9.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcome After Fetoscopic Laser Surgery for Twin-twin Transfusion Syndrome: A Systematic Review of Follow-up Studies from the Last Decade

Abstract: Objective: To review the literature on long-term neurodevelopmental outcome after fetoscopic laser surgery for twin-twin transfusion syndrome (TTTS). Methods: A literature search in PubMed, Embase, Emcare, Web of Science, Cochrane library, and Academic Search Premier was performed. Inclusion criteria were studies between 2009 and 2019 in TTTS-survivors treated with fetoscopic laser surgery and followed-up after the neonatal period with cognitive develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…The normal functioning of twins after TTTS syndrome in terms of cognitive and motor functions can be attributed to early tactile and vestibular stimulation in the prenatal period, which is consistent with studies indicating normal cognitive, motor, and emotional functioning [ 42 , 47 , 48 , 49 , 50 , 51 , 52 ]. The twins differ slightly in cognitive functioning and general intelligence: the functioning of K, the recipient, was at the upper limit of the average level, while that of B, the donor, was at the average level.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The normal functioning of twins after TTTS syndrome in terms of cognitive and motor functions can be attributed to early tactile and vestibular stimulation in the prenatal period, which is consistent with studies indicating normal cognitive, motor, and emotional functioning [ 42 , 47 , 48 , 49 , 50 , 51 , 52 ]. The twins differ slightly in cognitive functioning and general intelligence: the functioning of K, the recipient, was at the upper limit of the average level, while that of B, the donor, was at the average level.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, they may both have had occasional difficulties formulating longer verbal statements and performing tasks with several stages. Most studies do not report differences in long-term impairment between donor and recipient twins [ 52 ]. However, Polish studies thus far have found better functioning in the recipient [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to include a broad description of neurodevelopmental impairment, with speech and language disorders, attention deficit (hyperactivity) disorder, and fine motor impairment identified as the most common types. The findings of a 2020 systematic review of 24 studies included a mean prevalence of 5% for cerebral palsy compared to 1 in 90 (1%) in our study, and a mean prevalence of 10.5% for any neurodevelopmental impairment compared to our 31% [ 24 ]. Although most of the reviewed studies assessed for a limited number of impairments, Müllers et alreported a rate of 14.2% for neurodevelopmental impairment at a median age of four years that included cerebral palsy, speech and language delay, behavioural concerns such as autism, and mild motor delay [ 33 ].…”
Section: Discussionmentioning
confidence: 68%
“…We were able to associate the risk of long-term neurodevelopmental impairment in children that survived placental laser photocoagulation with maturity at delivery and neonatal wellbeing. Early birth gestation and low birthweight were similarly recognised as risk factors in studies included in two systematic reviews, the Knijnenburg et alreview [ 24 ], and a 2021 review by Hessami et al [ 35 ]. Higher Quintero TTTS stage at laser was determined to increase risk in 4 of 5 studies included in the Knijnenburg et alreview but was not significantly associated with neurodevelopmental impairment in the Hessami et alreview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation